How to improve the competences develoment in the e-learning? A practical experience in the strategic management subject - Eva María MORA-VALENTÍN; Marta ORTIZ-DE-URBINA-CRIADO (Education in the knowledge society, 2015)
The aim of this paper is to analyze the development of competences in the on-line learning through the activities proposed by the teacher in the teaching guide. To do this, we have made an exploratory study on the on-line subject of Strategic Management and Business Policy I taught in the Degree of Business Administration at the Rey Juan Carlos University. Our results have shown that there are differences between the perception of the teacher and student on the activities used to develop the competences. Therefore, the teacher should reformulate the activities it proposes to achieve the competencies and to define clearly each competence and how it is acquired.